Structure and Stimulus Familiarity: A Study of Memory in Chess-Players with Functional Magnetic Resonance Imaging - Campitelli, Guillermo; Gobet, Fernand; Parker, Amanda (The Spanish Journal of Psychology, 2005)
A grandmaster and an international chess master were compared with a group of novices in a memory task with chess and non-chess stimuli, varying the structure and familiarity of the stimuli, while functional magnetic resonance images were acquired. The pattern of brain activity in the masters was different from that of the novices. Masters showed no differences in brain activity when different degrees of structure and familiarity where compared; however, novices did show differences in brain activity in such contrasts. The most important differences were found in the contrast of stimulus familiarity with chess positions. In this contrast, there was an extended brain activity in bilateral frontal areas such as the anterior cingulate and the superior, middle, and inferior frontal gyri; furthermore, posterior areas, such as posterior cingulate and cerebellum, showed great bilateral activation. These results strengthen the hypothesis that when performing a domain-specific task, experts activate different brain systems from that of novices. The use of the expertsversus- novices paradigm in brain imaging contributes towards the search for brain systems involved in cognitive processes.